Interpretation of Dynamic Sediment Characteristic Based on Microtremor Analysis in Prambanan Region, Sleman Yogyakarta and Klaten Central Java, Indonesia - Hesti Hesti; Subagyo Pramumijoyo; Djoko Wintolo (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
Yogyakarta earthquake on Mei 27, 2006 caused Prambanan area get quite severe damage marked by damageof resident house and Prambanan Temple.This study was conducted using data of microtremorsingle station and Yogyakarta earthquake 27 May 2006. Data were analyzed with microtremor HVSR methods to get the value of the dominant frequency (fo) and amplication (Ao).Furthermore, calculated the value of peak ground acceleration (PGA) in the layers of sedimen bedrock and seismic vulnerability index (Kg) to get ground shear strain value. Prambanan area has a dominant frequency (fo) value ranges from 0.63-6.78 Hz. Ground shear strain valueranges from 3,55.10-5 - 4,04.10-2.Each of these factors is then mapped with a division of 4 zones is very high, high, medium, and low.Based on the analysis of all these factors Prambanan area is an area that is vulnerable to the risk of earthquake events.